Conditional Knockout of PKC-δ in Osteoclasts Favors Bone Mass Accrual in Males Due to Decreased Osteoclast Function - Li, Shangfu; He, Tianwei; Wu, Depeng; Zhang, Liangming; Chen, Ruiqiang; Liu, Bin; Yuan, Jinbo; Tickner, Jennifer; Qin, An; Xu, Jiake; Rong, Limin (Frontiers in Cell and Developmental Biology, 2020)
Protein kinase C delta (PKC-δ) functions as an important regulator in bone metabolism. However, the precise involvement of PKC-δ in the regulation of osteoclast remains elusive. We generated an osteoclast specific PKC-δ knockout mouse strain to investigate the function of PKC-δ in osteoclast biology. Bone phenotype was investigated using microcomputed tomography. Osteoclast and osteoblast parameters were assessed using bone histomorphometry, and analysis of osteoclast formation and function with osteoclastogensis and hydroxyapatite resorption assays. The molecular mechanisms by which PKC-δ regulated osteoclast function were dissected by Western Blotting, TUNEL assay, transfection and transcriptome sequencing. We found that ablation of PKC-δ in osteoclasts resulted in an increase in trabecular and cortical bone volume in male mice, however, the bone mass phenotype was not observed in female mice. This was accompanied by decreased osteoclast number and surface, and Cathepsin-K protein levels in vivo, as well as decreased osteoclast formation and resorption in vitro in a male-specific manner. PKC-δ regulated androgen receptor transcription by binding to its promoter, moreover, PKC-δ conditional knockout did not increase osteoclast apoptosis but increased MAPK signaling and enhanced androgen receptor transcription and expression, finally leding to significant alterations in gene expression and signaling changes related to extracellular matrix proteins specifically in male mice. In conclusion, PKC-δ plays an important role in osteoclast formation and function in a male-specific manner. Our work reveals a previously unknown target for treatment of gender-related bone diseases.